Environmental magnetism: Application to cave sediments - Aidona, E.; Pechlivanidou, S.; Pennos, Ch. (Bulletin of the Geological Society of Greece, 2013)
Environmental magnetism techniques allow a rapid, low cost and sensitive characterization of sediments and can be applied in a wide range of environments. More specific, magnetic properties can be successfully used to reconstruct paleoenvironmental and paleoclimatic conditions in rockshelter and cave sites. Cave sediments, imprint the environmental conditions at the Earth’s surface at the time of deposition since are well protected both at the interior and at the entrance of the cave systems. In addition, many cultural sequences and archaeological artifacts are well preserved in rockshelter and cave sediment records and can be effectively used for paleoenvironmental interpretations. In this study we present data from two different cave sites from Northern Greece. In the first cave (Maronia Cave) magnetic measurements were performed in two cores 80 and 90 cm, respectively, located inside the cave area. High values of magnetic susceptibility are directly linked with the human activity inside the cave, while lower values show deposition under infiltration and fluvial processes. In the second cave (Mikro Eptamilon Cave), magnetic susceptibility and frequency dependent magnetic susceptibility depicted from a sedimentary sequence with a thickness of 200 cm, located in the entrance of the cave. Results lead to conclusions concerning the velocity of the paleo-flow likely related to the paleoclimatic conditions that dominated the broader area.